PENERAPAN STRATEGI PEMBELAJARAN AKTIF QUICK ON THE DRAW UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIA SMA AL-HUDA PEKANBARU - Ningsih, Monalisa Septia Ningsih Septia; Copriady, Jimmi Copriady; Linda, Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The objective of the research is to achieve students learning mastery on the subject of chemical equilibrium in XI MIA class at SMA Al-Huda Pekanbaru trough the applying achive learning strategy Quick On The Draw. The research form is pra-experiment design with one-shot study case. The data were collected from September 2014 – June 2015. The population of the research is all of students in XI MIA SMA Al-Huda Pekanbaru which consists of 2 classes and the sample are the students in XI MIA 2 class that are selected randomly. Data were analysed to gain learning mastery in the competency knowledge, that is learning mastery individual (passed when the student reaches a value ≥ 2,67), learning mastery classical (passed if 85% of students reach 2,67), mastery of individual indicators (passed when 65% of students reach ≥ 2,67 in each indicator), mastery of each indicator (passed when 65% of students reach ≥ 2,67 in each indicator), and classical mastery indicator (passed when 75% of students reach the mastery of each indicator). Based on the final result by using mastery learning individual, 12 students are passed and 3 students did not pass, classical mastery learning gained 87.5%, individual mastery indicators is obtained by 4 students by passing all indicators and 3 students who did not pass, each mastery of indicator derived from 11 indicators, 9 indicators are passed 2 indicators are not pass and classical mastery learning gained 81.82%. The results showed that the application of active learning strategy Quick On The Draw can achieve student’s learning mastery on the subject of chemical equilibrium in XI MIA class at SMA Al-Huda Pekanbaru. Keywords : Quick On The Draw, Mastery Learning, Chemical Equilibrium